2017
DOI: 10.1002/ijc.30831
|View full text |Cite
|
Sign up to set email alerts
|

Complement component 1, q subcomponent binding protein (C1QBP) in lipid rafts mediates hepatic metastasis of pancreatic cancer by regulating IGF‐1/IGF‐1R signaling

Abstract: Pancreatic cancer shows a remarkable predilection for hepatic metastasis. Complement component 1, q subcomponent binding protein (C1QBP) can mediate growth factor-induced cancer cell chemotaxis and distant metastasis by activation of receptor tyrosine kinases. Coincidentally, insulin-like growth factor-1 (IGF-1) derived from the liver and cancer cells itself has been recognized as a critical inducer of hepatic metastasis. However, the mechanism underlying IGF-1-dependent hepatic metastasis of pancreatic cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 45 publications
(54 reference statements)
1
31
0
Order By: Relevance
“…A variety of signaling pathways have been reported to be involved in the development and progression of PDAC including mitogen-activated protein kinase (MAPK) [8] and Notch [9] signaling pathways, growth factors such as epidermal growth factor (EGF) [8], fibroblast growth factor (FGF) [10] and insulin-like growth factor 1 (IGF-1) [11]. Based on these findings, scientists have uncovered various biological targets, and developed several corresponding targeted therapies [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of signaling pathways have been reported to be involved in the development and progression of PDAC including mitogen-activated protein kinase (MAPK) [8] and Notch [9] signaling pathways, growth factors such as epidermal growth factor (EGF) [8], fibroblast growth factor (FGF) [10] and insulin-like growth factor 1 (IGF-1) [11]. Based on these findings, scientists have uncovered various biological targets, and developed several corresponding targeted therapies [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…And recent studies have con rmed that complement can promote tumor growth in mouse models (Markiewski and Lambris 2009). Moreover, in vivo and in vitro data show that tumor cells can activate complement (Bjorge, Hakulinen et al 2005, Corrales, Ajona et al 2012 and Shi et al (Shi, Fang et al 2017) reported that complement component 1, q subcomponent binding protein (C1QBP), in lipid rafts mediates liver metastasis of pancreatic cancer by regulating IGF-1 / IGF1R signaling. They reported that the expression of C1QBP in many human cancers is higher than that in normal tissues, including thyroid, lung, esophageal, gastric and colon cancer, and refer to previous reports that C1QBP mediates EGF induced chemotaxis and distant metastasis by activating receptor tyrosine kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial C1qbp may also be responsible for the tumour-promoting property by increasing the energy for the growth of the cells and allowing glutamine addiction 42 . In addition, C1qbp may also contribute to metastasis 37 , for example, insulin-like growth factor induced the transition of C1qbp to the plasma membrane in pancreatic cancer cells, which promoted hepatic metastasis 43 . Inhibition of C1qbp was reported to suppress the growth of the tumour cells, which presents C1qbp as a potential drug target 34,43,44 .…”
Section: Introductionmentioning
confidence: 99%